Failure Analysis on the Impressed Current Cathodic Protection of Wharf Steel Pipe Pile - LI Hai - hong, DENG Chun - lin, FANG Xiang (Cailiao Baohu)
The steel pipe piles of a coal wharf were protected by an impressed current cathodic protection system. After construction, it was found that the cathodic protection system was in a state of under - protection regardless of the adjustment of the output current. Therefore, the circuit layout, system components, electrical connection resistance and rectifier electrical parameters of the impressed current cathodic protection system were tested in detail. Results showed that the system had faults such as partial failure of the auxiliary anode, large electrical connection resistance, and incorrect display parameters of the rectifier. However, the series connection of the confluence circuit should be the main reasons for the failure of the system, and the too small cross - sectional area of the connecting cable conductor further aggravated the deterioration of the system. The simulation results were also consistent with this conclusion.